Rare bird documentation form for Peregrine Falcon at Loess Hills, 1985 - Moore, Francis L.et al (1985)
Rare bird documentation form for a Peregrine Falcon at Loess Hills in Fremont County, IA on April 28, 1985. Epson - sheet feed